Veno-Venous Extracorporeal Membrane Oxygenation terhadap Pemulihan Pasien COVID-19 Disertai Acute Respiratory Distress Syndrome - Yuniyas Ihsanidar; Tuti Herawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of veno-venous Extracorporeal Membrane Oxygenation on the recovery of COVID-19 patients with Acute Respiratory Distress Syndrome and the factors that support its point. The method used in this research is a literature search from several online databases. The results showed that from the ten articles reviewed, the effectiveness of veno-venous Extracorporeal Membrane Oxygenation on the recovery of COVID-19 patients with Acute Respiratory Distress Syndrome was supported by the workings of veno-venous Extracorporeal Membrane Oxygenation itself and the role of perfusion/perfusionist nurses in its management. One way of working veno-venous Extracorporeal Membrane Oxygenation in cases of severe respiratory failure is to facilitate the direct exchange of oxygen and carbon dioxide from the blood. Meanwhile, a perfusionist is responsible for the operation of the ECMO machine and patient care and monitoring while the machine is installed. In conclusion, overall, the article describes the effectiveness of veno-venous Extracorporeal Membrane Oxygenation on the recovery of COVID-19 patients with Acute Respiratory Distress Syndrome. Keywords: ARDS, COVID-19, Nurse, VV ECMO